Siswa Sd Menggunakan Smartphone dalam Pembelajaran Online - Mohammad Salehudin; Marniah; Hariati (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2020)
The use of smartphones at the age of elementary school (SD) students can have a negative effect on the growth of knowledge and learning activities. However, with the implementation of home learning and online learning in Indonesia today, elementary students have a lot of time using smartphones to study or using smartphones in a positive way. The purpose of this study was to determine the use of smartphones for elementary students in online learning. This study used a quantitative approach to survey methods and selected a random sample of 124 respondents who lived in urban areas, elementary school students in grades 3-6 and had given answers to a questionnaire given in the form of google form. The research instrument was adapted from several literatures. The instrument is made in 10 question items. The study was analyzed with quantitative statistical descriptions using SPSS version 24. The results found that 31 students had smartphones and 94 students used smartphones belonging to their parents, siblings and other people in online learning. The time spent studying is between 5-6 hours. Elementary students use smartphones in the